Democratic Critiques of the Institutions and Processes of Neoliberal International Economic Integration: An Assessment - Robinson, Ian (Cahiers de recherche sociologique, 1995)
Three basic types of democratic critique have been levelled against "neoliberal" economic integration agreements such as the NAFTA and the Single European Act. One type holds that the institutions created to oversee the integration process are deficient on democratic grounds. This paper summarizes and evaluates this type of democratic critique. It is argued that allegations that the European Union suffers from a "democratic deficit" are not very convincing. However, criticisms of the lack of openess and due process in neoliberal dispute resolution processes are more persuasive. Arguments for a treaty ratification process that includes a referendum are also convincing.